2022
DOI: 10.2967/jnumed.122.264423
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Coronary Artery Calcium Scores from SPECT/CT Attenuation Maps Improve Prediction of Major Adverse Cardiac Events

Abstract: Low-dose ungated CT attenuation correction (CTAC) scans are commonly obtained with SPECT/CT myocardial perfusion imaging. Despite the characteristically low image quality of CTAC, deep learning (DL) can potentially quantify coronary artery calcium (CAC) from these scans in an automatic manner. We evaluated CAC quantification derived with a DL model, including correlation with expert annotations and associations with major adverse cardiovascular events (MACE). Methods: We trained a convolutional long short-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The performance of our model could be further improved by utilizing data from other imaging modalities 26 . For instance, computed tomography attenuation correction scans could be used to automatically calculate calcium score, which could be included in the time-to event model 27 . Finally, the usefulness of the time-to-event predictions has not been evaluated in prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of our model could be further improved by utilizing data from other imaging modalities 26 . For instance, computed tomography attenuation correction scans could be used to automatically calculate calcium score, which could be included in the time-to event model 27 . Finally, the usefulness of the time-to-event predictions has not been evaluated in prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…The model incorporates CAC, which is currently not available for most patients presenting with suspected CAD. However, CAC can also be estimated from standard nongated, noncontrast chest computed tomography 30 , 31 or quantified automatically from nongated computed tomography attenuation scans using artificial intelligence 32 , 33 , 34 ; therefore, CAC assessment could potentially be available in a much larger proportion of patients. For example, Peng et al recently demonstrated that CAC could be derived automatically from chest computed tomography scans performed for a variety of reasons to help predict cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Our formerly validated deep learning model was used for CAC segmentation and scoring. 17,18 To segment heart mask and CAC on CTAC images, two convolutional long short-term memory (convLSTM) networks were tested externally on data (10,480 CTAC scans) from 4 different sites. To automatically obtain CAC scores from the deep learning segmentation, established methods were used.…”
Section: Automated Coronary Artery Calcium Scoringmentioning
confidence: 99%